The adventures of Don Quixote - Cervantes Saavedra, Miguel de, 1547-1616.; Cohen, John M. (New York : Penguin, 1950)
Tells the story of the adventures of Don Quixote, the visionary idealist and Sancho Panza, the practical realist.
Wilson's Senior High School.
Young Adult
Keywords: Don Quixote (Fictitious character) -- Fiction; Knights and knighthood -- Fiction; Panza, Sancho (Fictitious character) -- Fiction; Don Quixote (Fictional character) -- Fiction; Knights and knighthood -- Fiction; Panza, Sancho (Fictional character) -- Fiction; Spain -- Fiction; Spain -- Fiction